IMPROVING DESCRIPTIVE WRITING ABILITY THROUGH MIND MAPPING - Khusniyah, Nurul Lailatul (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2019)
The study aims to get the effect of the mind mapping on students descriptive writing ability and the process of mind mapping implementation in writing descriptive learning. The research study is qualitative and quantitative research through action research method. The sample was taken by 34 students. The validity of data used credibility, transferability, dependability, and conformability. The process of collecting data used test, observation, and interview. The researcher used Independent sample t-test to analyze the differences of students’ ability before and after using mind mapping. The finding of analysis that mind mapping implementation has increase the students’ motivation of descriptive writing learning. They can make a good imagination in writing. The t-test result is t-stat (5.38) > t-table (1.99). It means that there is a significant difference was found in descriptive writing ability before and after using mind mapping.